Thermal Denaturation Kinetics of Whey Protein and Maltodextrin Mixture - Nuraini, Mohd Yusoff; Jolius, Gimbun; M. M., Yusoff (Springer, 2013)
This chapter presents thermal denaturation studies of whey protein and maltodextrin mixture. Different compositions of whey protein–maltodextrin mixture were exposed to various temperature and holding time. The main protein contents, i.e., β-lactoglobulin (β-lg) and α-lactalbumin (α-lac) before and after heat exposures were analyzed using ultra-performance liquid chromatography. Significant decreases in protein contents were found as temperature and holding time increases. Addition of maltodextrin to whey protein solution reduces the protein denaturation significantly. Formulation of 9:1 WPI to maltodextrin ratio was shown to reduce α-lac denaturation by up to 15.1 % and even higher reduction for β-lg which is up to 74.6 % after 20 min at 70 °C. Results from UPLC analysis of the residual native protein suggests that the thermal sensitivity of β-lg was higher compared with α-lac. Over 97 % of β-lg was denatured after 20 min as opposed to about 60 % for α-lac at 80 °C. Protein denaturation was also observed to increase proportionally with temperature. Results from this work may be useful to preserve the protein content in milk during processing involving thermal exposure.